Novel AVPR2 mutations in congenital nephrogenic diabetes insipidus: clinical characteristics and genetic analysis - Xue, Kunjiao; Wu, Jin; Lyu, Juanjuan; Sun, Xiaomei; Liu, Ying; Yuan, Chuanjie (Frontiers in Pediatrics, 2025)
ObjectivesCongenital nephrogenic diabetes insipidus (NDI) is a rare hereditary disorder caused by mutations in two critical genes: arginine vasopressin receptor 2 (AVPR2) and aquaporin 2 genes (AQP2). Mutations in AVPR2 gene, which are predominantly X-linked, account for a significant proportion of cases, particularly in men. Nevertheless, research on this condition in the western Chinese population remains limited.MethodsEleven participants from nine families with NDI were screened for AVPR2 mutations. Their clinical features were documented, and genotype–phenotype associations were investigated.ResultsThis study included 11 pediatric patients with congenital NDI, comprising 10 boys and 1 girl. They were diagnosed between 1 month and 7 years of age. The clinical presentations included growth retardation, polydipsia, and polyuria in all patients (11), hypernatremia in 10, renal pelvis dilation in 4, absence of posterior pituitary high signal on magnetic resonance imaging in 3, unexplained fever in 3, and recurrent vomiting in 1 and mental retardation each in 1 patient. Genetic analysis revealed eight AVPR2 mutations among the 11 patients with congenital NDI, 3 of which were novel: p.Ile46Serfs*145, p.Ile177del, and p.Ser327Ilefs*30.ConclusionsIn the largest case series of congenital NDI caused by AVPR2 mutations in the western Chinese population, eight AVPR2 mutations were identified, including three that were novel. This study enhances the existing literature by elucidating the clinical manifestations of congenital NDI by analyzing 11 cases and by identifying three novel mutation sites, thereby augmenting the genetic understanding of this condition.